Patients' experiences and perspectives of living with CKD - Tong, Allison; Sainsbury, Peter; Chadban, Steven; Walker, Rowan G; Harris, David C; Carter, Stacy M; Hall, Bronwyn; Hawley, Carmel; Craig, Jonathan C (American journal of kidney diseases, 2009)
Explicit incorporation of patients' values and preferences is important in health care decision making. However, there are few data about this topic for patients with chronic kidney disease (CKD). We conducted 9 focus groups (3 each for CKD stages 1 to 5, CKD stage 5D, and CKD stages 1 to 5T). Five major themes were identified: (1) personal meaning of CKD, (2) managing and monitoring health, (3) lifestyle consequences, (4) family impact, and (5) informal support structures. Patients had to adjust to the disruptive and permanent implications of the illness on their physical health, identity, emotions, family, lifestyle, relationships, and employment. The overwhelming fatigue, complex treatment regimens, side effects, and liquid and diet restrictions constrained patients' lives. Patients appreciated specialist care, but described the health care system as nonintegrated and believed they received insufficient information and psychosocial support. Choice of treatments was based on lifestyle, family impact, and physical comfort, seldom on clinical outcomes. Time was needed to comprehend the diagnosis, cope with uncertainty, integrate their treatment regimen into their daily routine, and reestablish a sense of normality in their lives. Rather than focusing on clinical targets, greater attention may need to be given to providing information and psychosocial and practical support at a patient-level not organ-specific level, to maximize patient quality of life.